Oriented assembly of copper metal–organic framework membranes as tandem catalysts to enhance C–H hydroxyalkynylation reactions with regiocontrol. Issue 4 (3rd January 2020) - Huang, Chao; Zhu, Kaifang; Lu, Guizhen; Zhang, Yingying; Wang, Dandan; Zhang, Dianbo; Mi, Liwei; Hou, Hongwei
Abstract : The continuous and uniform MOF-based membrane (1a ) as a highly efficient heterogeneous catalyst was fabricated on porous Cu foam to significantly outperform bulk crystals 1 to execute C–H hydroxyalkynylation reactions with regiocontrol. Abstract : Constructing well-organized metal–organic framework (MOF) membranes with a uniform and continuous nanoarchitecture is an effective strategy for the functionalization of MOF-based heterogeneous catalysts. In this work, by employing surfactant PVA (poly(vinyl alcohol)) as a soft-template, a moderate synthetic approach was adopted to obtain a Cu-MOF (1, [Cu(BBDC)(azobpy)(H2 O)] n, H2 BBDC = 4′-benzoyl-(1, 1′-biphenyl)-3, 5-dicarboxylic acid; azobpy = 4, 4′-azopyridine) for building highly ordered Cu-MOF membranes (1a ) with good control of the morphology and thickness on the surface of macroporous Cu foam, which could facilitate the growth of homogeneous and high-quality Cu-MOF membranes. Furthermore, the catalytic performance of Cu-MOF membranes 1a was superior to that of large sized 1 for tandem three-component C–H hydroxyalkynylation reactions, because the Cu-MOF membranes could afford a functionalized and tunable platform with the benefit of readily accessible active sites to promote tandem reactions by minimizing the diffusion distance but did little for their regioselectivity.